La justice militaire belge en 14-18 : Représentations culturelles et réalités quantitatives - Benoît Amez (Amnis)
Quite a lot of Belgian combatants from World War I showed how the military justice was repressive and utterly unequal. But some of them also pointed the failure of the military justice in crisis, unable to deal with the situation. The sentenced combatants escaped their  condemnation to death, and were sent to the back of the front line, safe from  bomb attacks. However the penal reality showed that the number of sentences was constantly relatively important throughout the conflict. On the other hand sentences to death and above all executions were unusual, and the great majority of the sentences were not entirely enforced. The sentenced soldiers were massively sent to disciplinary companies. The aim was to give them the opportunity of a second chance and above all to foil the plans of those who tried to escape from the dangers on the front line. The Belgian soldiers criticized the military justice for being an integral part of the military system. Nevertheless the combatant reports didn’t question the war itself. So the mobilization of the Belgian soldiers during the conflict seemed to be a mixture of adherence and duress. Strange though, the obedience to the army seemed to be accepted by the great majority of the combatants.